Assessing The Impact of Personality Characteristics on Students’ Visual Perception for Landscapes (EMARA: Indonesian Journal of Architecture, 2017)
As landscape plays a crucial role in people’s lives, it is of great importance that landscape is designed based on people’s interest. Therefore, identification of the landscapes that people prefer and the factors that influence their perception are imperative. This research attempts to investigate the contribution of personality characteristics towards students’ landscape perception in Isfahan, Iran. In this aspect, students’ characteristics of extroversion/ introversion, intelligence, and creativity were measured by using Cattell’s 16PF Questionnaire. Also, the respondents were asked to express their feeling of satisfaction and happiness towards six common landscape types of Iran, by rating 30 images of mountainous, urban, forest, desert, water, and farmland landscapes. The results of Pearson Correlation Coefficient indicated that extroverted students have a greater feeling for both mountainous and urban landscapes than introverts. Also, less creative students preferred mountainous, urban, and farmland landscapes. Moreover, perception for farmland landscape was negatively correlated with intelligence among students.